The Effect of Human Resources Competence, Internal Control System and Accounting Understanding Based on SAK-ETAP on the Quality of Financial Statements - I Gusti Ngurah Bagus Surya; Muhyarsyah Muhyarsyah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study uses the SAK ETAP model to examine the effect of increasing human resource skills, internal control processes, and accounting expertise on the credibility of financial statements. The results of 99 questionnaires given to cooperative banks in DKI Jakarta were collected using quota sampling. This research uses Data Quality Test, Assumption Test, Model Feasibility Test, and Hypothesis Testing Procedure. According to the findings of this study, HR competence greatly enhances the credibility of financial reports. Knowledge, ability, and efficacy of a manager in monitoring cooperative human resources are closely related to the quality of cooperative financial reports; thus, it is very important for managers to have a thorough understanding of how cooperatives function. The existence of an effective internal control system has a significant impact on the quality of financial reporting. Standard Operating Companies, if implemented effectively, can help cooperatives improve the quality of their financial reports and get closer to their goals. By understanding accounting based on SAK ETAP, the quality of financial reporting can be significantly improved. How well cooperative management can identify, measure, and disclose transactions in cooperatives with post/account transactions that must be recorded to prepare complete financial statements and describe the financial condition of the cooperative which is actually an indication of the quality of the financial statements produced. can help cooperatives improve the quality of their financial reports and get closer to their goals. By understanding accounting based on SAK ETAP, the quality of financial reporting can be significantly improved. How well cooperative management can identify, measure, and disclose transactions in cooperatives with post/account transactions that must be recorded to prepare complete financial statements and describe the financial condition of the cooperative which is actually an indication of the quality of the financial statements produced. can help cooperatives improve the quality of their financial reports and get closer to their goals. By understanding accounting based on SAK ETAP, the quality of financial reporting can be significantly improved. How well cooperative management can identify, measure, and disclose transactions in cooperatives with post/account transactions that must be recorded to prepare complete financial statements and describe the financial condition of the cooperative which is actually an indication of the quality of the financial statements produced.